2017
DOI: 10.1111/hiv.12564
|View full text |Cite
|
Sign up to set email alerts
|

Screening for human papillomavirus, cervical cytological abnormalities and associated risk factors in HIV‐positive and HIV‐negative women in Rwanda

Abstract: The currently used quadrivalent vaccine may be insufficient to give satisfactory HPV coverage in Rwanda. HPV Screening may be effective to identify women at risk of developing cervical cancer, particularly if provided to high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 40 publications
7
26
0
3
Order By: Relevance
“…While the rates of AIDS‐related cancers such as Kaposi's sarcoma have decreased since the introduction of combination antiretroviral therapy (cART), a similar trend has not been observed for cervical cancer . The HIV‐infected cohort in the present study was well monitored and the majority of women had normal CD4 counts and low HIV viral loads at baseline . This indicates that immune surveillance may still be compromised in HIV‐positive patients on cART.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…While the rates of AIDS‐related cancers such as Kaposi's sarcoma have decreased since the introduction of combination antiretroviral therapy (cART), a similar trend has not been observed for cervical cancer . The HIV‐infected cohort in the present study was well monitored and the majority of women had normal CD4 counts and low HIV viral loads at baseline . This indicates that immune surveillance may still be compromised in HIV‐positive patients on cART.…”
Section: Discussionsupporting
confidence: 53%
“…The impact of the vaccination programme on cervical cancer incidence is not known, as it takes several years for cervical cancer to develop. We showed that the percentage of women undergoing cervical cancer screening was low . Monetary issues and not being educated about the importance of screening were reasons for not undergoing cervical cancer screening .…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations